Sustainable procurement behavior: a case of government departments - Nadeem, Shahid; Mohamad, Mohamad Hanapi; Nik Abdullah, Nik Ab. Halim (International Economic Society, 2017)
This paper discusses the concept of sustainable procurement behavior (SPB) and the effects of personal values, leadership style and awareness on SPB. As the SPB became increasingly important in implementation for sustainable procurement practices, the paper aims to present the review of the existing literature on SPB and study the factors that can influence the SPB of procurers. The paper based on review of past literature, conceptualizes that personal values, awareness, leadership are significantly related to SPB and organizational culture moderates the relationship among personal values, leadership style, awareness and SPB. The results of this conceptual paper are likely to provide important insights to managers, policy-makers and researchers to further understand the factors which effect the SPB and improve the implementation of SPP practices.